2017
DOI: 10.5301/hipint.5000458
|View full text |Cite
|
Sign up to set email alerts
|

Stable Migration Pattern of an Ultra-Short Anatomical Uncemented Hip Stem: A Prospective Study with 2 Years Radiostereometric Analysis Follow-Up

Abstract: Like many other uncemented stems, the Proxima showed early migration up to 3 months hereafter osseointegration seems to have occurred. The achieved stability and clinical outcomes indicate favorable early results for this stem in younger patients who have good bone quality and average BMI. We found, however, the surgical technique to be slightly more demanding compared to conventional stems owing to the unique implant design that necessitates specific adjusted femoral cutting and broaching procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
1
12
1
Order By: Relevance
“…Osseointegration can be assumed if an RSA study shows stable migration values after 3 months. Nevertheless, the subsidence was higher than reported in other recent studies, where Y-translation is between -0.03 mm and -0.99 mm at 24 months (Nysted et al 2014, Weber et al 2014, Nebergall et al 2016, Mahmoud et al 2017, Hoornenborg et al 2018, Sesselmann et al 2018, Klein et al 2019, Kruijntjens et al 2020. Nebergall et al (2016) (the Taperloc stem), reported a single outlier of -0.9 mm with the rest of the cohort in a range of -0.1 mm to -0.2 mm.…”
Section: Primary Outcomecontrasting
confidence: 64%
“…Osseointegration can be assumed if an RSA study shows stable migration values after 3 months. Nevertheless, the subsidence was higher than reported in other recent studies, where Y-translation is between -0.03 mm and -0.99 mm at 24 months (Nysted et al 2014, Weber et al 2014, Nebergall et al 2016, Mahmoud et al 2017, Hoornenborg et al 2018, Sesselmann et al 2018, Klein et al 2019, Kruijntjens et al 2020. Nebergall et al (2016) (the Taperloc stem), reported a single outlier of -0.9 mm with the rest of the cohort in a range of -0.1 mm to -0.2 mm.…”
Section: Primary Outcomecontrasting
confidence: 64%
“…15 Early studies of the Proxima stem have focused on surgical technique, 16 migration pattern and bony integration using radiostereometric analysis and/or dual energy X-ray absorptiometry (DXA). [17][18][19] There have been several clinical studies regarding this implant, but they are limited by either the length of follow-up 20 or the patient number. 21 Thigh pain is a common complaint following uncemented hip arthroplasty using conventional stems, with up to one in eight patients affected, some of which eventually require revision.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmoud et al 83 investigated the migration of Proxima in 28 hips followed for two years after surgery. The mean subsidence and varus tilt were low, such as 0.22 ± 0.28 mm and 1.04 ± 0.81.…”
Section: Stem Features and Outcomesmentioning
confidence: 99%